Contingent National Belonging: The Perceived Fit and Acceptance of Culturally Different Peers Predicts Minority Adolescents' Own Belonging - Gharaei, Nadya; Phalet, Karen; Fleischmann, Fenella (Frontiers in Psychology, 2018)
Prevailing definitions of national identities in Europe equate belonging to the nation with ‘fitting in’ culturally and leave immigrant minorities who are culturally different from the majority group struggling to belong. The present study focuses on an under-researched minority perspective on the intersubjective cultural contents of the national identity. We propose that minorities’ national belonging is contingent on their perception that minority peers who deviate from the majority culture are accepted as real nationals. Our study aims to establish (a) minority perceptions of the national fit and acceptance of culturally different peers, and to test (b) the consequences of perceived fit and acceptance for minority adolescents’ own national belonging, and (c) its affordances by the local peer context. Drawing on a large random sample of 1489 Moroccan and Turkish minority youth (aged 12-18) and their peers across 312 classes in 63 Belgian schools, we varied cultural difference from the majority in three vignettes describing imagined acculturating peers. Minority participants rated to what extent they saw each peer as a real national (perceived fit) and whether other nationals would accept this peer (perceived acceptance). As a measure of their own national belonging, they indicated their national self-identification. Additionally, the multi-level design included classroom contextual measures of majority peer presence and peer acculturation norms (peer norm of heritage culture maintenance). As expected, minority youth who perceived better national fit of culturally different peers, self-identified more strongly as nationals than those who perceived worse fit. This association was not explained by their own acculturation attitudes. In line with the contextual affordance of national fit, only in classes with majority peers, minority youth perceived higher national fit and acceptance of culturally different peers when peer norms supported the maintenance of a distinct heritage culture. We conclude that the national belonging of minority youth is contingent on the peer context through the perceived fit and acceptance of culturally different peers.